2021
DOI: 10.1080/21655979.2021.1976712
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits progression of glioma via regulating the HMMR antisense RNA 1/microRNA-7/cyclin dependent kinase 4 axis

Abstract: Sevoflurane (Sev) is a volatile anesthetic that can inhibit tumor malignancy. Glioma is a main brain problem, but the mechanism of Sev in glioma progression is largely unclear. This study aims to explore a potential regulatory network of long noncoding RNA (lncRNA)/microRNA (miRNA)/mRNA associated with the function of Sev in glioma progression. LncRNA HMMR antisense RNA 1 (HMMR-AS1), miR-7 and cyclin-dependent kinase 4 (CDK4) abundances were examined via quantitative reverse transcription polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Sevoflurane is an inhalational anesthetic with common application in surgery. Studies have shown that sevoflurane affects cancer progression and inflammations via mediating signaling pathways and gene expressions [ 7 , 8 ]. It altered pathophysiological situations of brain, which leads to neuroinflammation and results in neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane is an inhalational anesthetic with common application in surgery. Studies have shown that sevoflurane affects cancer progression and inflammations via mediating signaling pathways and gene expressions [ 7 , 8 ]. It altered pathophysiological situations of brain, which leads to neuroinflammation and results in neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…SEV has been shown to regulate the expression of non-coding RNAs, such as microRNAs and long noncoding RNAs (lncRNAs) (Shen et al, 2021;Zhao et al, 2021;Jiang et al, 2021;Bao et al, 2021) which play a vital role in the regulation of RNA transcription (Ratti et al, 2020). Thus, we speculate that SEV may upregulate UAF1 transcript and protein levels through regulating the expression of non-coding RNAs.…”
Section: Discussionmentioning
confidence: 81%
“…The western blot assay was conducted as previously reported ( 25 ). Total protein was isolated from U251 and A172 cell lines with RIPA lysis buffer (Invitrogen) and quantified using the bicinchoninic acid (BCA) method.…”
Section: Methodsmentioning
confidence: 99%